Activated flux TIG welding of Inconel 718 super alloy in presence of tri-component flux. Issue 2 (25th January 2019) - Kumar, Hemant; Ahmad, Gulshad Nawaz; Singh, N. K.
ABSTRACT: In this study, we have explored the influence of newly developed tri-component oxide flux (Cr2 O3, FeO, and MoO3 ) on weldability, bead geometry, weld pool temperature variation, and mechanical strength of Inconel 718 welded joints. Moreover, the influence of used flux on weld pool, the surface morphology of electrode and penetration capability of tungsten inert gas (TIG) welding on Inconel 718 plates have been well elucidated. Results indicate that the flux mixture significantly increases the penetration depth as well as aspect ratio almost 200% as compared to conventional TIG welding. The arc constriction caused by newly developed oxide flux upsurges the heat density and the weld pool temperature of joints. The alloying effect caused by entrapped oxide particles greatly improves the hardness as well as the tensile strength of joints. The reported reinforcement in the welding performance may increase potential utility of the developed methods for real-world applications.